Um autorretrato de Primo Levi: as raízes literárias da narrativa de Auschwitz - Zuin, João Carlos Soares [UNESP] (My University, 2013)
Th e anthology La ricerca della radice written by Primo Levi allows the reader to understand the intellectual infl uences received throughout his life. Th e aim of this paper is to establish analytic relation between the authors contained in the personal anthology of Primo Levi and his historical narrative about Auschwitz.

A antologia La ricerca della radice escrita por Primo Levi permite ao leitor compreender as infl uências intelectuais recebidas ao longo de sua vida. O objetivo deste artigo é estabelecer relações analíticas entre os autores contidos na antologia pessoal de Primo Levi e a sua narrativa histórica sobre Auschwitz.
Keywords: Primo Levi; Auschwitz; Modernity; Concentration camps; Dehumanization; Primo Levi; Auschwitz; modernidade; Campos deconcentração; Desumanização